Improving Relationships by Elevating Positive Illusion and the Underlying Psychological and Neural Mechanisms - Song, Hongwen; Zhang, Yongjun; Zuo, Lin; Chen, Xueli; Cao, Gui; d’Oleire Uquillas, Federico; Zhang, Xiaochu (Frontiers in Human Neuroscience, 2019)
Romantic relationships are difficult to maintain novel and exciting for long periods of time, and individuals in love are known to engage in a variety of efforts to protect and maintain their romantic relationship. How to protect and maintain these relationships more effectively has however plagued people, psychologists, and therapists. Intimate partners typically perceive their relationship and their partners in a positive light or bias, a phenomenon called positive illusion. Interestingly, higher levels of positive illusion between partners have been associated with decreased risk for relationship dissolution, as well as higher satisfaction, and less conflict or doubt in relationships. These findings indicate that elevating positive illusions amongst romantic partner may be benefit and improve romantic relationships. In the present article, we discuss the solving the paradox of positive illusion. As positive illusion may have relationship-enhancing attributes, we discuss the psychological and neural mechanisms that may underlie positive illusion. By elucidating the mechanisms underlying positive illusion, we shine a spotlight on potential future directions for research that aims to improve positive illusion and thus enhance the satisfaction and longevity of romantic relationships.